Recent Advances in Electron Donor‐Acceptor (EDA)‐Complex Reactions involving Quaternary Pyridinium Derivatives - Saxena, Barakha; Patel, Roshan I.; Sharma, Anuj (Advanced synthesis & catalysis, 2023)
Quaternary pyridinium compounds are valuable intermediates in organic synthesis, which have gained immense popularity in the synthetic community. The application of transition metal or photoredox catalysis in transforming quaternary pyridinium compounds into various C−C and C−X bonds is well established. A majority of these methods require high temperatures, expansive catalysts, and delicate conditions for successful execution. On the other hand, the use of transition metal‐free and photocatalysis‐free strategies in constructing C−C and C−X bonds using quaternary pyridinium derivatives has been sought‐after. In this context, the electron‐donor‐acceptor (EDA)‐complex reactions have emerged as a state‐of‐the‐art organic synthetic methodology, which do not require any photocatalyst for their successful execution. EDA‐complex photochemistry takes advantage of the electron‐acceptor ability of quaternary pyridinium derivatives, which can quickly generate a radical precursor via the deaminative process. These newly generated radical intermediates are useful in several valuable transformations. We hereby, in this review, discuss an area of major progress in EDA‐complex mediated reactions involving quaternary pyridinium compounds with mechanism, substrate scope, and limitations.